2015
DOI: 10.1134/s0021364014240059
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature Aharonov-Bohm effect in transport through a single-channel quantum ring

Abstract: We overview transport properties of an Aharonov-Bohm interferometer made of a single channel quantum ring. Remarkably, in this setup, essentially quantum effects survive thermal averaging: the high temperature tunneling conductance G of a ring shows sharp dips (antiresonances) as a function of magnetic flux. We dis cuss effects of the electron-electron interaction, disorder, and spin-orbit coupling on the Aharonov-Bohm transport through the ring. The interaction splits the dip into series of dips broadened by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…We have demonstrated the existence of interference-induced effects, which are robust to the temperature, i.e., survive under the condition Eq. 5, and can therefore be obtained for relaxed experimental conditions (for discussion of this regime in conventional interferometers, see refs 41,[58][59][60][61] ). Specifically, we have found that G is structureless in ballistic case but shows periodic dependence on dimensionless flux ϕ = Φ/Φ 0 (here, Φ 0 = hc/e is the flux quantum), with the period 1/2, in the presence of a single magnetic impurity in one of the interferometer's shoulders.…”
Section: Modelmentioning
confidence: 99%
“…We have demonstrated the existence of interference-induced effects, which are robust to the temperature, i.e., survive under the condition Eq. 5, and can therefore be obtained for relaxed experimental conditions (for discussion of this regime in conventional interferometers, see refs 41,[58][59][60][61] ). Specifically, we have found that G is structureless in ballistic case but shows periodic dependence on dimensionless flux ϕ = Φ/Φ 0 (here, Φ 0 = hc/e is the flux quantum), with the period 1/2, in the presence of a single magnetic impurity in one of the interferometer's shoulders.…”
Section: Modelmentioning
confidence: 99%
“…We see that sharp antiresonances appear at half-integer and integer values of the flux, φ by contrast to conventional interferometers, where only half-integer resonances exist [29]. The difference is related to the absence of backscattering by non-magnetic contacts in the case of helical edge states [31].…”
Section: B Almost Closed Interferometermentioning
confidence: 62%
“…The high-temperature regime, T ∆, was already studied for single-channel AB interferometers made of conventional materials [26][27][28][29][30] and it was demonstrated that flux-sensitive interference effects survive in this case. Recently, we discussed high-temperature electron and spin transport in AB interferometers based on helical edge states of TI [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the coupling strength α drops out from the result of Eq. (38). Thus, the radiation-induced contribution to current might be large even in the weakcoupling regime, and decays as T −1 in contrast to the persistent current contribution which decays exponentially with temperature.…”
Section: A Isolated Ring Adiabatic Radiation Switchingmentioning
confidence: 97%
“…To conclude the comparison of I per and I rad , we note that persistent current might show up indirectly at high temperatures. In particular, it was demonstrated in a series of publications [36][37][38] that the tunneling current through a single-channel quantum ring is blocked by persistent current. This effect, caused by an interplay of quantum interference and charge quantization, has been named the persistent-current blockade (PCB) in analogy with the well-known Coulomb blockade.…”
Section: Introductionmentioning
confidence: 99%